The role of institutional and economic factors in the strategic use of non-GAAP disclosures to beat earnings benchmarks - Isidro, H. (2015)
We use hand-collected data for a sample of large European firms to investigate the influence of countries’ institutional and economic factors on managers’ non-generally accepted accounting principles (GAAP) disclosures. We find that managers are more likely to use non-GAAP measures to meet or beat earnings benchmarks that GAAP earnings would miss in countries with efficient law and enforcement, strong investor protection, developed financial markets, and good communication and dissemination of information. We also find that managers in countries with developed institutional and economic conditions are more likely to adjust non-GAAP earnings for recurring expenses such as R&D, depreciation, and stock-based compensation expenses. Our findings suggest that in environments in which there is more pressure to achieve earnings benchmarks and less opportunity to manipulate GAAP earnings, managers use more non-GAAP earnings disclosures to meet the benchmarks